On this issues of developing mathematical communication abilities of 10th form pupils - Zybartas, Saulius (Lietuvos matematikos rinkinys, 2003)
The last Education reform in Lithuania has been going on for about 15 years. One of the most important parts of the reform is development and implementation of modern, valid, reliable and objective evaluation and assessment system. This paper will focus on assessing general, mathematical skills (enabling skills) of 10th grade students: assessing skills of mathematical communication.